1868 Fla. Laws 2538 - (:unkn) unknown (My University, 1868)
Persons Engaged in Criminal Offence, Having Weapons, ch. 7, § 10: Prohibited the carrying of a slungshot, metallic knuckles, billies, firearms or other dangerous weapon if arrested for committing a criminal offence or disturbance of the peace. Punishable by imprisonment up to 3 months or a fine up to $100.
Keywords: CARRY - INTENT TO COMMIT CRIME